The Influence Of Social Media Marketing And Electronic Word Of Mouth On The Decision To Purchase Mixue Products In Harapan Baru Bekasi - Alif Syaridwan; Dewi Sri Wulandari; Bayu Seno Pitoyo (Draf Solusi Indonesia, 2024)
This research aims to determine the influence of the social media marketing and e-Word of Mouth on purchasing decisions for mixue products in Harapan Baru Bekasi. This type of research is quantitative and the sampling technique used in this research is convenience sampling technique. The sample used was 130 respondents taken by distributing questionnaires. Data analysis test results using Multiple Linear Regression. The results in this research show that Social Media Marketing has a partially positive and significant influence on Purchasing Decisions, likewise with Electronic Word of Mouth there is a partially positive and significant influence on Purchasing Decisions.